Adsorption and Removal of Antibiotic Pollutants using CuO−Co3O4 Co‐modified Porous Boron Nitride Fibers in Aqueous Solution. Issue 11 (14th November 2022) - Bai, Wenjuan; Wang, Bozheng; Yang, Shaobo; Yan, Song; Cao, Chaochao; Zhou, Zheng; Ji, Jiawei; Guo, Kai; Tang, Chengchun
Abstract: The presence of antibiotic contaminants in aqueous environment already poses significant risks to ecological sustainability, biodiversity and human public health and safety. Therefore, it is urgent to develop practical water pollution control technologies and new materials. Here, we prepared CuO−Co3 O4 co‐modified porous boron nitride fibers (P−BNFs) for the adsorption and removal of tetracycline antibiotics (TCs) in aqueous environment. The prepared adsorbents were characterized by XRD, FTIR, XPS, SEM, TEM and BET, and the adsorption behavior was explored by batch experiments. The results show that the removal percentage for doxycycline (DC) reaches 98.68 %, which was much higher than that of P−BNFs, and the modification results of P−BNFs with CuO or Co3 O4 alone. After five regeneration cycles, the removal rate of DC by CuO−Co3 O4 /P−BNFs was still as high as 89.33 %. This is promising and indicates that the prepared CuO−Co3 O4 /P−BNFs adsorbent has good renewable recycling performance and practical application prospects. Abstract : A bimetallic oxide co‐modified CuO−Co3 O4 /P−BNFs material is reported in this work, which significantly improved the adsorption performance on TCs, and the removal rate of TCs was more than twice that of P−BNFs under the same conditions.